Validity and Practicality of Online Learner Worksheets Based on Students' Mathematical Problem Solving Ability - Rahmi, Hanifatul (JDIME: Journal of Development and Innovation in Mathematics Education, 2023)
Learner Worksheets (LKPD) are teaching materials that encourage students to learn independently that are methodically created based on a specific syllabus, packaged in a certain time unit, and displayed by utilizing online learning technology. The purpose of this project is to create an online Student Worksheet (LKPD) for students that focuses on answering math problems. It uses a development research (R&D) approach with the 4D model (Define, Design, Develop, Disseminate) in its creation. This research was conducted to determine the validity and practicality of LKPD based on mathematical problem solving on line and angle material in Sungai Penuh City. The instruments used are validation sheets and practicality sheets. Based on the results of the Material Expert test, an average score of 93% was obtained in the Very Valid category, and the results of the Media Expert test reached an average score of 91.81% in the Very Valid category. The results of the math teacher's response received a score of 100% in the Very Practical category and the results of student responses received an average score of 89.37% in the Very Practical category. Based on these results, it can be concluded that the online Student Worksheet (LKPD) based on mathematical problem solving is valid and practical for use as a learning resource. A valid and practical online LKPD can help improve learning effectiveness by allowing students to learn independently and interactively with teaching materials designed according to their needs.